Optimisation of Petroleum Product Transportation by Multimodal Transport During Martial Law - Zelenko, Yuliia V.; Cherkudinov, Volodymyr E.; Tarasov, Vsevolod; Soroka, Maksym L. (Springer Science and Business Media LLC, 2024)
ENG: The hostilities in Ukraine have significantly changed the logistics of petroleum product supply. Overland routes via EU countries, in particular Poland, Romania and the Baltic states, have become the main transport solution. Rail transport remains the main mode of transportation for petroleum products, providing significant volumes, but faces the challenges of low capacity and delays at the borders. Road transport is showing growth due to the flexibility required in the crisis. The relevance of the work is determined by the need to increase the efficiency of logistics in the face of rising costs of transport resources and economic challenges that may be associated with a large number of both direct and indirect factors (economic, technological, political, security, etc.), the analytical set of which indicates the vulnerability of the security system for the transport of high-risk cargo.
Yu. Zelenko: ORCID 0000-0001-5551-0305; V. Cherkudinov: ORCID 0000-0003-3164-0329; M. Soroka: ORCID 0000-0002-0558-6077
Keywords: petroleum products; multimodality; energy effi ciency; environmental friendliness; railway; car; КЕЦБ (ДІІТ); КПММ (ДІІТ)